KONSELING SEBAYA SEBAGAI ALTERNATIF PENYELESAIAN MASALAH BAGI SISWA INTROVERTED - ahmad Ario Akbar; Aisha Zuleyka; Nuri Cholidah Hanum; Yesi Nila Sari; Caraka Putra Bhakti (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
Peer counseling is an alternative approach in counseling services to help individuals carried out by peers. Peer counseling is seen as important because in today's era, individuals talk more about the problems they face with their peers than with parents or teachers. Peer counseling makes it easier for individuals to talk more comfortably to peers. Therefore, this counseling is very suitable for individuals, especially those who have an introverted personality. Peers who do counseling require competencies that must be possessed to support the success of counseling and create good relationships with friends, especially individuals who have introverted personalities. The method used in this research is a literature study by collecting various kinds of journals related to the subject of the research. The results based on this study can be concluded that peer counseling is an alternative approach that has effectiveness for individuals with introverted personalities. By using these alternatives, individuals with introverted personalities have the convenience of telling stories and are able to overcome the problems they face.